Peran Media Kartu "Cerdas" dalam Meningkatkan Kemampuan Kosakata Anak TK A di Semarang Tengah - Alice Zellawati; Siska Adinda; Prabowo Putri (Jurnal Ilmiah Psikologi MIND SET, 2017)
Developing vocabulary skills in pre-school children is one of the most decisive aspects of development for young children. This study aimed to optimize vocabulary skills in early childhood through interactive learning model with CERDAS card media. The research was conducted in 20 schools of TK A Central Semarang. The research method used was quasi-experimental method with one group pretest-posttest design. The results of this study indicated that there was a very significant children. In addition, the study also showed that there was a difference in vocabulary skills between boys and girls.